2000
DOI: 10.1046/j.1365-2168.2000.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre, randomized clinical trial of primary versus secondary sigmoid resection in generalized peritonitis complicating sigmoid diverticulitis

Abstract: Primary resection is superior to secondary resection in the treatment of generalized peritonitis complicating sigmoid diverticulitis because of significantly less postoperative peritonitis, fewer reoperations and shorter hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(114 citation statements)
references
References 22 publications
1
106
0
7
Order By: Relevance
“…Although the superiority of an approach with primary resection has been established in multicenter randomized studies over the traditional threestage treatment (diversion, resection, and reanastomosis) [1], the indication to perform a primary anastomosis versus an end-colostomy (Hartmann's procedure; HP) is still under debate.…”
mentioning
confidence: 99%
“…Although the superiority of an approach with primary resection has been established in multicenter randomized studies over the traditional threestage treatment (diversion, resection, and reanastomosis) [1], the indication to perform a primary anastomosis versus an end-colostomy (Hartmann's procedure; HP) is still under debate.…”
mentioning
confidence: 99%
“…The multiple variable logistic regression analysis estimated odds ratios and 95% confidence intervals for days from admission for each outcome adjusted for confounders. The solution to the regression equation was used to predict the average probability of each outcome for each day following admission (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Average predicted values for each day were plotted to show the trend over 1 -20 days.…”
Section: Discussionmentioning
confidence: 99%
“…Diverticulitis complicated by pericolic or pelvic abscess may be treated with intravenous antibiotics and possible image guided drain placement (6). Patients with peritonitis require emergent surgical resection (6,8).…”
Section: Introductionmentioning
confidence: 99%
“…One of the first published reviews of emergency surgery for perforated diverticular disease reported improved mortality and morbidity when the colon was resected compared with procedures in which the colon was left in the abdomen [30]. A subsequent randomized trial reported that primary resection was associated with significantly lower rates of postoperative peritonitis and early re-operation when compared with initial suture of the perforation and diverting colostomy followed by secondary sigmoid resection [31].…”
Section: Primary Anastomosis Versus Hartmann's Proceduresmentioning
confidence: 99%